Effect of Fuel Injection Pressure, Isobutanol and Ethanol Addition on Performance of Diesel-biodiesel Fuelled D.I. Diesel Engine. (2015) - Sastry, G.R.K.; Deb, Madhujit; Panda, Jibitesh Kumar
Abstract: Biodiesel with additives is generally preferred for improvement of performance and emission characteristics of diesel engines. Higher fuel injection pressure is effective in improving the performance and reducing emissions. In the present work, Isobutanol and ethanol as additives to the diesel-biodiesel blends was investigated experimentally in a direct injection diesel engine. Isobutanol (A1) and Ethanol (A2) were added 5%-10% by volume to diesel-biodiesel blends and the performance and emissions characteristics at different injection pressures viz. 200, 225, 250 and 275 bars were studied.From the results, it was found that nozzle opening injection pressure could be increased up to 250 bar, as a result of which brake thermal efficiency and fuel economy of the engine were improved. Further, Carbon Monoxide (CO) emissions opacity was reduced significantly. However, Nitrogen Oxide (NOx ) emissions decrease in some blends marginally.